(untitled) (Fiep Bulletin - online, 2015)
This article comes to grips with Michel Maffesoli´s ideas about the post modernistic society and the relation of adventure and risk sports at this moment, where it seems to have had a renascence of an archetypical structures, archaic ones. There was a preference of outdoors sports, involving the air, like free flying and free fall. On land, involving mountaineering and tracking. In the water, rafting and also skate street, an adventure sport practiced in urban areas.This study has a qualitative aspect and its aims are: (a)identify the presence of the characteristics at the post modernity on the speeches of the practitioners of adventure and hazard sports in nature and in the urban environment; (b) verify the relations existed on the speeches of these practitioners of these sports that make use of air, land and water.This study is characterized by a meta analyses , beginning by studies interpretations of Katia Passos (2005)Treking, Manuela Gonsales (2004). Free fall, Fabiana Rodrigues (2004). Rafting, Vera L.Costa (1999), Mountaineering , Maria Regina Costa (2004); Skate Street, Luciana Abdala (2001), Free flying, and the analyses of the context beginning by the speeches of these practitioners of hazard and adventure sports. In a initial analysis, we verified that the hazard and outdoors sports match with post modernistic characteristic, conforming qualified in previous studies mentioned. They were times of the tribes, of nomadism, errant, sensible reason of adventure. The places make the links. It is noticed that these characteristics emerged from a significant way on the practitioners of risk and outdoors sports.